Health and medical education - going back to the way Family Medicine - Dalla, Marcelo Dala Bernardina (2004)
The current health’s conceptions and health education, still conformed in XVI’s Century. Flexner report, was the most important document, in the earlier XX’s Century, it’s define the definitive hospitals incorporation as the axle of the learning and the practical medicine. Today there are some ways to break the distance in the patients and medical relations, as well as the rescue of the natural environment of cure, as the family medicine, who ayms the individual and its family attention but not only its illnesses.